The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/v12070742
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of the Safety and Efficacy of BAFASAL® Bacteriophage Preparation for the Reduction of Salmonella in the Food Chain

Abstract: Bacteriophages are bacterial predators, which are garnering much interest nowadays vis-à-vis the global phenomenon of antimicrobial resistance. Bacteriophage preparations seem to be an alternative to antibiotics, which can be used at all levels of the food production chain. Their safety and efficacy, however, are of public concern. In this study, a detailed evaluation of BAFASAL® preparation was performed. BAFASAL® is a bacteriophage cocktail that reduces Salmonella in poultry farming. In vivo acute an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 83 publications
1
24
0
Order By: Relevance
“…In particular, we were interested in whether this agricultural bacteriophage mixture, used as a feed additive in poultry farming to prevent and eliminate Salmonella , would display off-target effects on the human microbiome. It has been reported that BAFASAL significantly reduces Salmonella levels in poultry, reducing mortality and improving feed conversion rates [12]. These types of therapeutic and prophylactic agricultural bacteriophages are important tools to address the critical on-going need to maintain food safety, improve the health of animals in our food chains, and reduce human morbidity and mortality due to consumption of contaminated food.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, we were interested in whether this agricultural bacteriophage mixture, used as a feed additive in poultry farming to prevent and eliminate Salmonella , would display off-target effects on the human microbiome. It has been reported that BAFASAL significantly reduces Salmonella levels in poultry, reducing mortality and improving feed conversion rates [12]. These types of therapeutic and prophylactic agricultural bacteriophages are important tools to address the critical on-going need to maintain food safety, improve the health of animals in our food chains, and reduce human morbidity and mortality due to consumption of contaminated food.…”
Section: Discussionmentioning
confidence: 99%
“…To date, rodent models have been used extensively to examine bacteriophage safety as therapeutics in medicine and agriculture. Oral administration of different anti- Salmonella bacteriophage mixtures into mice did not result in gross clinical changes or mortality [12, 28]. Additionally, mice treated with a bacteriophage therapeutic against E.coli also did not exhibit any toxic effects [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Monofunctionalization of MOP might be difficult to achieve Isolation of different diastereomers of Fe-MOP is not feasible Paramagnetic metal cation present at the MOP might alter the relaxation time T 1 and depolarize Xe As of now, there are no reports available on in vitro and in vivo toxicity of MOP Modular hosts (micelles & liposomes) Easy production of micelles and liposomes with controllable size and layers Encapsulation of hundreds of hosts in a liposome is possible e.g., with cryptophanes in liposomes Offers possibilities to indirectly prepare targeted hosts by functionalizing the outer layer of liposomes with desired target moieties Hosts such as cryptophanes can be tethered to the phospholipid or to micelle surfactant molecule prior to producing the micelles and liposomes Dual modality biosensors can be established using cryptophanes and dyes for 129 Xe HyperCEST NMR and optical imaging Multiplexing approach might be feasible upon introduction of different hosts inside the liposomes Stable over months with fabricated size and encapsulated cargo, e.g., Xe hosts, drug etc. Modular hosts serve as ideal models for studying membrane-embedded Xe and its host interactions and membrane fluidity Generally, micelles and liposomes are considered to be non-toxic both in vitro and in vivo [ 248 , 249 ] These modular hosts are mostly utilized as drug carriers thereby leading to successful drug delivery in vivo. Unlabeled modular hosts exhibit only medium to fast Xe exchange due to rather loose transient binding Tethering Xe hosts, e.g., cryptophanes, onto the phospholipids, micelles arm might not be straightforward.…”
Section: Aspects Of 129 Xe Biosensor Designmentioning
confidence: 99%
“…Generally, micelles and liposomes are considered to be non-toxic both in vitro and in vivo [ 248 , 249 ]…”
Section: Aspects Of 129 Xe Biosensor Designmentioning
confidence: 99%